2016
DOI: 10.1002/jclp.22292
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Institutional Betrayal Predict Suicidal Self-Directed Violence Among Veterans Exposed to Military Sexual Trauma

Abstract: Perceptions regarding institutional betrayal appear to be highly relevant to MST and its sequelae. These findings underscore the importance of Veterans' perceptions of the military institution's efforts to prevent and respond to MST to individual recovery from sexual trauma. Additional research regarding the association between institutional betrayal and health-related outcomes is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
98
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 110 publications
(121 citation statements)
references
References 34 publications
(47 reference statements)
13
98
1
Order By: Relevance
“…Considering that MST is often perpetrated by fellow service members that one works with and resides near, the context of MST may have differed in important ways from other trauma that female SM/Vs experience (e.g., combat). Relatedly, a possible explanation for the more severe outcomes associated with attributing PTSD symptoms to MST (relative to other types of trauma) involves the institutional context in which MST occurs and the feelings of betrayal that may ensue when MST occurs within the context of a previously trusted institution (Monteith, Bahraini, Matarazzo, Soberay, & Smith, ). Additional explanations may include stigma (Blais et al., ), thwarted belongingness (Monteith et al., ), or the possibility that females with MST as the source of their index trauma are more likely to delay treatment (Washington, Bean‐Mayberry, Riopelle, & Yano, ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that MST is often perpetrated by fellow service members that one works with and resides near, the context of MST may have differed in important ways from other trauma that female SM/Vs experience (e.g., combat). Relatedly, a possible explanation for the more severe outcomes associated with attributing PTSD symptoms to MST (relative to other types of trauma) involves the institutional context in which MST occurs and the feelings of betrayal that may ensue when MST occurs within the context of a previously trusted institution (Monteith, Bahraini, Matarazzo, Soberay, & Smith, ). Additional explanations may include stigma (Blais et al., ), thwarted belongingness (Monteith et al., ), or the possibility that females with MST as the source of their index trauma are more likely to delay treatment (Washington, Bean‐Mayberry, Riopelle, & Yano, ).…”
Section: Discussionmentioning
confidence: 99%
“…The sample was restricted to users of VA care, which limits the generalizability of study findings. A positive history of MST is based on self‐report and prior research shows that some veterans decline to disclose their true MST status (Blais et al, ; Monteith, Bahraini, Matarazzo, Soberay, & Smith, ). Because of the use of the MST screening tool as our indicator of a positive history of MST, we were unable to determine if variations in MST (e.g., inappropriate verbal remarks versus sexual assault) were uniquely associated with eating disorder diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…as well as saying the victim did not take make proactive choices to prevent it from happening (Monteith, Bahraini, Matarazzo, Soberay, and Smith, 2016). The study showed a clear association between the perception of betrayal and the symptoms of PTSD and depression, based on the MST and how it was handled by military authorities.…”
Section: Psychological Impact and The Reporting With Rank Structurementioning
confidence: 86%
“…Importantly, this data speaks only for the veterans who have chosen to seek VA health care; but not for those who haven't. (Monteith, Bahraini, Matarazzo, Soberay, & Smith, 2016).…”
Section: Section 1: How Common Are Sexual Assaults In the Military?mentioning
confidence: 99%
See 1 more Smart Citation